Interplay of regional oceanography and biogeochemistry on phytoplankton bloom development in an Arctic fjord. (30th September 2020) - Singh, Archana; David T., Divya; Tripathy, Sarat C.; Naik, Ravidas K.
Abstract: Ongoing sea-ice melting and associated environmental changes influence the bloom phenology and biogeochemistry of the Arctic Ocean. Kongsfjorden, a fjord in Svalbard, has already undergone the transition of being sea-ice covered in winter to sea-ice free, and now stands vulnerable to Atlantic water intrusion and glacier melting. We monitored physical and biogeochemical variables in the fjord between July 2015 and July 2016 using Indian Arctic subsurface mooring in Kongsfjorden. The year-round records of nitrate represent the first reported sensor-based observation in the region. Here, we used the high-resolution time-series of chlorophyll a, nitrate, dissolved oxygen, photosynthetically active radiation, turbidity, temperature, and salinity to study their interactions and assess how do they relate to the development of phytoplankton bloom. Results indicated a high nitrate concentration (up to 13.3 μM) and near-zero chlorophyll a in winter. The spring bloom was spotted from mid-April to the first week of June (up to 7.2 μg/L chlorophyll a at 25 m), however, with discontinuities due to high winds events. The chlorophyll a was negatively correlated with nitrate (r = −0.7, p < 0.001). Further, we observed temperature, salinity, and density characteristic of Atlantic water at 25 m and 35 m in autumn and early-winter, which coincided with nitrate peaks. This indicated nitrate supply by Atlantic inflow during the non-bloom period. We say that the features of the bloom start evolving from rather quiescent autumn and winter before it reaches an active state in spring-summer. Year-round high-resolution observations are crucial to study phytoplankton bloom phenology as any shift or change in the phenology will affect higher trophic levels and biogeochemical cycles. Highlights: In 2016, spring bloom at subsurface occurred from late-April to June, peaked in May. Chlorophyll a values in spring as high as 7.2 μg/L and 4.8 μg/L at 25 m and 35 m, respectively. High wind events disrupted the subsurface spring bloom. Annual nitrate cycle showed Atlantic water inflow contributes to subsurface nitrate.